(untitled) (Fiep Bulletin - online, 2013)
The dance provides favorable experience for the development of children who are bearers or not of the Down Syndrome (DS), for involving the child in their sphere, in socio-affective and psychomotor aspects. This case study had as an objective to identify the lifestyles of bearers of the DS and to describe how activities such as, music may alter aspects in their development, in an integrated environment. The subjects analyzed were two children bearers of the DS, one of the male sex and another of the female, 6 and 9 years old, respectively, who attended a school of education for children in Santa Cruz do Sul/RS. Questionnaires were applied to the parents and teachers of a class and, following weekly sessions, of 30 to 40 minutes, for 11 weeks, which stated history of the sessions, re-creative dominance, development of bodily expression, coordination, rhythm, balance and spatial perception, through methods directive with music, in an integrated environment with the classmates. After each session, observations of the involvement and participation of each student were made. The results point a good profile of lifestyle, once they demonstrate social integration, absence of illnesses and follow up with different health professionals. In the intervention sessions, the students with the DS presented differentiated behavior, being that the boy was motivated and autonomous and the girl with reduced bodily expression and mood oscillations, alternating movements in the evolutions and involutions, being that the firsts manifested predominantly in the activities with music. In such case, it can be concluded that music is a positive instrument in the work with the DS, yet suggesting that the sessions occur with weekly frequency and longer duration, once it was small improvements were observed in the development of two children with the DS, in an environment integrated of classroom.